Studying Library Technicians’ Professional Lives Using Life History - Hicks, Deborah (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Within the libraries and other information organizations, paraprofessionals have taken on ever more important roles. Given the prominence of paraprofessionals in the LIS workplace, their organizational roles and career paths are understudied. Using life history methodology, this study will address this gap in the LIS literature. Au sein des bibliothèques et autres organismes d’information, les paraprofessionnels assument des rôles de plus en plus importants. Compte tenu du nombre de paraprofessionnels dans le milieu des BSI, leurs rôles organisationnels et leurs plans de carrières demeurent sous étudies. À l’aide d’une méthodologie du cycle de vie (life history), cette étude comble un vide dans la littérature des BSI.